Identify drying kinetic parameter using the Newton Model, Modified Page Model and Two Term Model for banana and guava / Siti Fazilawati Jaafar - Jaafar, Siti Fazilawati (Research Management Institute (RMI), 2009)
The characteristic drying of banana and guava was determined. This characteristic of drying was measured using the mathematical model drying Newton Model, Modified Page Model and Two Term Model. The parameter from the three models determined using the Sum Square Error (SSE) and Minimum Sum Square Error (MSSE). Drying of banana and guava was investigated from the experiment and the parameter each model was determined depend the drying parameter example temperature, velocity and relatively humidity during drying process. For experiment banana, the temperature used at 40 ° C, 50 ° C and 60 ° C, constant velocity and humidity at 1.8 m/s and 40 % for each temperature. For guava experiment, used the 50 ° C, 60 ° C and 70 ° C and constant velocity and humidity at 2m/s and 40%.